2016
DOI: 10.1136/lupus-2016-000168
|View full text |Cite
|
Sign up to set email alerts
|

ECG non-specific ST-T and QTc abnormalities in patients with systemic lupus erythematosus compared with rheumatoid arthritis

Abstract: ObjectivesCardiovascular disease (CVD) is a leading cause of death in systemic lupus erythematosus (SLE) and in rheumatoid arthritis (RA). Although only explored in one study, ECG non-specific ST-T abnormalities, in addition to corrected QT-interval (QTc) prolongation, were recently reported in an SLE inception cohort. Importantly, these ECG abnormalities are known predictors of CVD mortality in the general population, yet their prevalence in patients with established SLE has not been evaluated.MethodsWe cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
23
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 47 publications
3
23
3
Order By: Relevance
“…However, the two groups of patients studied by Geraldino-Parrilla et al 21 are very different, maybe too much, in terms of sex and ethnicity, and this could have significantly biased the results. In particular, in the general population it is well-established that female sex is associated with longer QTc duration (accordingly QTc prolongation cut-offs are different in males vs females) and higher TdP risk, via complex effects of sexual hormones on cardiac ion currents 3…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…However, the two groups of patients studied by Geraldino-Parrilla et al 21 are very different, maybe too much, in terms of sex and ethnicity, and this could have significantly biased the results. In particular, in the general population it is well-established that female sex is associated with longer QTc duration (accordingly QTc prolongation cut-offs are different in males vs females) and higher TdP risk, via complex effects of sexual hormones on cardiac ion currents 3…”
mentioning
confidence: 95%
“…In a recent publication in Lupus Science and Medicine , Geraldino-Parrilla et al 21 analysed ECG repolarisation parameters in a cross-sectional study involving 189 patients with autoimmune chronic inflammatory diseases, 50 affected with SLE and 139 with RA. The authors reported that non-specific ST-T abnormalities were significantly more common (∼fivefold), and mean QTc significantly longer (∼25 ms) in SLE when compared with patients with RA.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We excluded patients with alcohol-related or inflammatory liver diseases in order to avoid association of these conditions to the ECG patterns discovered. C-reactive protein levels have been shown to predict prolonged QT intervals in patients with systemic lupus erythematosus [34], rheumatoid arthritis [35] and patients with other connective tissue diseases [36]. A possible explanation for the better correlation between QT interval and biologic parameters in our study could be the very restrictive selection of patients, excluding, at our best, many possible reasons for altered ECG traces.…”
Section: Discussionmentioning
confidence: 68%
“…The high frequency of sinus bradycardia, sinus tachycardia, right bundle branch block, ST interval and T waves changes were seen in RA and SLE patients. Steroid therapy was probably responsible for producing the slowly ascending modify ST-T changes and previously reported increase of ST-T changes in RA and SLE [18] [19] [20]. In a recent study, we found 12 patients with abnormal chest X-ray with cardiomegaly and pulmonary artery hypertension.…”
Section: Discussionmentioning
confidence: 93%